Livestock production in central Mali: Sheep husbandry in the traditional sector - Wilson, R.T. (1985)
Describes traditional sheep husbandry in Central Mali with particular reference to breeds & their distribution; management systems & population demography of flocks; reproductive performance, growth rate & liveweight at dif. ages, and meat, milk & fiber yields.